Internet of Things Enabled Adjustable Ramp System for Productivity Enhancement of Micro, Small and Medium Enterprises - Akhil Sharma; Balbir Singh; Prabir Sarkar (Engineering Proceedings, 2024)
The industry usually faces a problem during the loading/unloading of finished products and raw materials from one place to another when both places are at different elevations. As trucks are of variable height and industry loading bays are at different elevations, it is not possible to drive the pallets effectively into freight, which results in decreasing loading/unloading efficiency of small concerns. In this paper, an adjustable height ramp system for increasing production efficiency and improving the industrial working environment was developed using a linear actuator and automation system for the safe loading and unloading of pallets. This adjustable ramp will help to increase the productivity of micro, small and medium enterprises (MSMEs), and it will provide a safe working environment. Using an adjustable ramp will help create a bridge between industry loading bays and freight, and it will also resolve the issue of different heights of both by making a path between them. The Internet of things (IoT)-enabled lifting and downward movement of the ramp is attempted for oil/air filter MSMEs.